Stenochironomus munteanpurin sp. n., a new leaf-mining species from Brazil (Diptera: Chironomidae) - Amora, Gizelle (Zootaxa, 2020)
Stenochironomus munteanpurin sp. n. is described and illustrated in all life stages, except eggs, from Brazil. The male is very similar to Stenochironomus quadrinotatus Borkent, 1984 due to same overall pattern of pigmentation. The new species can be distinguished from the other related species principally in immature stages: larva with labral lamella arranged in two groups with one or two conical-shaped teeth, spicules of pecten epipharyngis arranged in a row, unequal and irregularly distributed sizes, SI bifurcated, SII pinnate, SIII pinnate setae and, larval exuviae is compacted; pupa with shagreens being in all TI, less number of hooklets in TII, TVII without shagreens and presence of shagreen in conjunctive III/IV and IV/V. Adult male is very similar to the one of S. quadrinotatus but can be distinguished by combination of the TIX with more than 25 setae medially and phallapodeme curved anteriorly. The new species were collected in the following Brazilian states: Rio de Janeiro, Santa Catarina, Bahia and Acre. Copyright © 2018 Magnolia Press.